Song Guides and Prostitution (Analysis of the Phenomenon of Deviations in Criminological Perspectives) - Agustin, Dewi; Syafitri, Linda; Muhaimina, Annisa; Kholik, Noor (Law Research Review Quarterly, 2020)
In this day and age work is an important part of human life. The difficulty of employment causes people to do everything they can to earn a living. One of them is working as a song guide at karaoke. The task of a Song Guide in accordance with the procedure is only as a customer guide while karaoke and offering food and beverage products owned by the karaoke. But sometimes the Song Guide does not only work like an existing procedure, but sometimes does work outside the procedure, such as accompanying customers to drink liquor, even by serving customers in serving the sexual desires of the customers.